2018
DOI: 10.1080/1059924x.2018.1470047
|View full text |Cite
|
Sign up to set email alerts
|

Job Resources and Work Engagement among Finnish Dairy Farmers

Abstract: The results indicate that the family, working with cattle, healthy farm animals, a reasonable workload, and a sustainable farm economy have the capacity to create positive impacts on well-being among dairy farmers. Well-being on farms is a part of sustainable food production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The mean value of WE in the total sample of this study was 3.32 (SD 1.13), which was the same as Sakurai et al [ 29 ] surveyed Kindergarten teachers. When compared with previous Japanese research [ 30 , 31 , 32 ], in which the mean value of the nurse survey was 2.68 points, dairy employees were 2.9 points, and SME employees were 2.92 points, participants of this study showed higher WE. This could be affected by the company’s higher motivation to participate in this study.…”
Section: Discussioncontrasting
confidence: 60%
“…The mean value of WE in the total sample of this study was 3.32 (SD 1.13), which was the same as Sakurai et al [ 29 ] surveyed Kindergarten teachers. When compared with previous Japanese research [ 30 , 31 , 32 ], in which the mean value of the nurse survey was 2.68 points, dairy employees were 2.9 points, and SME employees were 2.92 points, participants of this study showed higher WE. This could be affected by the company’s higher motivation to participate in this study.…”
Section: Discussioncontrasting
confidence: 60%
“…The respondents were asked to assess 8 job characteristics concerning workload, loneliness, and societal job demands, with a scale 1 (not strenuous at all) to 7 (very strenuous). See more detailed descriptions (Kallioniemi et al, 2016(Kallioniemi et al, , 2018. We included two job demand factors in the model, namely "workload," "societal job demands" and lack of resource "loneliness."…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on pay satisfaction and work engagement was carried out in countries including Malaysia (Memon, Salleh & Baharom, 2017); South Korea (Jung & Yoon, 2015); Vandenberghe & Tremblay, 2008); Finland (Kallioniemi, et al 2018) and career satisfaction in Nigeria (Adekola, 2011). Researches on job resources and work engagement were done on the level of interpersonal and social relations (Akinbobola & Nwankwo, 2017;Kallioniemi, et al 2018); the level of the work organized in an organization using paramiliatary organization (Akinbobola & Akinwole, 2017); and the level of the task (Akinbobola & Teluwo, 2018;Hakanen, Perhoniemia, & Toppinen-Tannera, 2008). The present study is on the organizational level of job resources using pay satisfaction.…”
Section: Statement Of Problemmentioning
confidence: 99%